Time–place learning in wild, free-living hummingbirds. (June 2015) - Tello-Ramos, Maria C.; Hurly, T. Andrew; Higgott, Caitlin; Healy, Susan D.
Abstract : Animals can learn to revisit locations at which foraging resources will renew over time. This ability is known as 'time–place' learning. Although there is clear evidence for time–place learning from animals trained and tested in the laboratory, not all species learn time–place tasks with similar ease. Since hummingbirds feed from food sources that are constant in space and that renew with time, it seems plausible these birds might learn time–place associations and do so readily. Here, then, we tested whether wild, free-living rufous hummingbirds, Selasphorus rufus, could learn the time and place at which four artificial flower patches were rewarded. Flowers in each of the four patches contained reward for only 1 h each day but the time and sequence in which patches were rewarded were repeated across days. Most birds learned when to visit each patch. To determine whether the birds used ordinal or circadian timing to choose the correct patch at the correct time, we ended the experiment with a single test trial in which we presented the patches (all flowers empty) only at the fourth hour of the day. The birds visited neither the patch that was normally rewarded first (daily ordinal timing) nor the fourth patch (time of day). These results suggest that the time component of the time–place learning in these birds requires both ordinal and circadian information. Highlights: Hummingbirds learned when and where to look for a reward. Some birds learned the time–place association after just 1 day of training. Birds use the time of day and the order of an event to visit the correct location.